Socioeconomic Status and Parental Lifestyle Are Associated With Vascular Phenotype in Children - Köchli, Sabrina; Endes, Katharina; Grenacher, Julia; Streese, Lukas; Lona, Giulia; Hauser, Christoph; Deiseroth, Arne; Zahner, Lukas; Hanssen, Henner (Frontiers in Public Health, 2021)
Background/Aims: Socioeconomic barriers and lifestyle conditions affect development of cardiovascular disease in adults, but little is known about the association of parental lifestyle and education with childhood health. We aimed to investigate the association of socioeconomic status (SES), migration background, parental physical activity (PA) and smoking status with micro-and macrovascular health in children. Methods: In 2016/2017, 833 school children (aged 7.2 ± 0.4 years) in Basel (Switzerland) were screened for retinal arteriolar-to-venular ratio (AVR), pulse wave velocity (PWV), SES, migration background and parental PA as well as smoking status. Results: High parental PA levels were associated with a favorable higher AVR (p = 0.020) and lower PWV (p = 0.035), but not independent of parental smoking status. Children with parents who smoked had a higher PWV [4.39 (4.35–4.42) m/s] compared to children with non-smoking parents [4.32 (4.29–4.34) m/s, p = 0.001]. Children of parents with a low household income had a higher PWV [4.36 (4.32–4.41) m/s] compared to children of parents with a high household income [4.30 (4.26–4.34) m/s, p = 0.033]. Low parental educational level was associated with a lower AVR [0.86 (0.85–0.88)] compared to children with highly educated parents [AVR:0.88 (0.87–0.88), p = 0.007; PWV: 4.33 (4.30–4.35) m/s, p = 0.041]. Children with a European background showed a higher AVR [0.88 (0.87–0.88)] compared to non-European children [AVR: (0.86 (0.85–0.87), p = 0.034]. Conclusion: Parental PA is associated with better macro- and microvascular childhood health. However, the positive association is lost when parental smoking is considered in the analysis. Socioeconomic factors seem to associate with subclinical vascular alterations in children. Primary prevention programs should focus on including parental lifestyle interventions and educational programs to reduce the burden of lifestyle-associated barriers in order to improve cardiovascular health during lifespan. Clinical Trial Registration:ClinicalTrials.gov Exercise and Arterial Modulation in Youth, https://clinicaltrials.gov/ct2/show/NCT02853747, NCT02853747.